Chromium-free Dacromet coating, coating preparation method and application thereof

By adding photocatalyst and metal slurry to the chromium-free dacrocoal coating, the coating with photocatalytic function is prepared, which solves the problem of insufficient corrosion resistance of the existing coating and achieves a more efficient anti-corrosion effect of steel components.

CN119592208APending Publication Date: 2025-03-11ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing chromium-free dacrocoated coatings are insufficient to meet the long-term anti-corrosion needs of steel components in power transmission and transformation equipment.

Method used

A chromium-free dacroleum coating with photocatalytic function is prepared by spraying technology to enhance the density and shielding ability of the coating.

Benefits of technology

It improves the corrosion resistance of the coating, extends the service life of steel components, reduces the risk of corrosion, is easy to operate and is easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592208A_ABST
    Figure CN119592208A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metal anticorrosive paints, and discloses a chromium-free Dacromet paint, a coating preparation method and application thereof, the chromium-free Dacromet paint comprises the following raw materials by weight: 17-50 parts of a silane hydrolysate containing a photocatalyst, 27-56 parts of metal slurry, 0.6-1 part of a thickener, and 0.6-1.2 parts of an antifoaming agent, and the photocatalyst is carbon nitride C3N4. The chromium-free Dacromet coating is prepared by using the silane hydrolysate containing the photocatalyst, so that the prepared chromium-free Dacromet coating has a photocatalysis effect, the photocatalyst generates photo-generated electron-hole pairs under the irradiation of sunlight, and photo-generated carriers migrate to the surface of the material through the interior of the material, so that the chromate-free Dacromet coating is formed. An electron-rich area is formed on the metal surface to prevent the metal from generating electron-losing corrosion, and meanwhile, the coating can participate in the oxidation-reduction reaction of water on the surface of the coating, so that the photolysis target of water molecules is realized, the corrosion of a steel base material is inhibited, and the corrosion resistance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal anticorrosion coatings, and in particular to a chromium-free Dacromet coating, a coating preparation method and applications thereof. Background Art

[0002] Steel components of power transmission and transformation suffer from corrosion due to long-term exposure to the natural environment. For example, the connecting fittings and fasteners used to connect insulators in transmission lines, which can bear large mechanical loads, are operated outdoors all year round and are affected by the natural environment such as rain, snow, wind and frost. The surface is very prone to corrosion, and the corrosion rate is generally fast. In addition, it is inconvenient to maintain at high altitudes. If effective protection is not carried out, the components will corrode and fail in a short period of time, causing power grid operation failures, which greatly affects the safe operation level of the transmission line.

[0003] At present, almost all steel components of power transmission and transformation equipment in my country use hot-dip galvanizing as the main protective technology. The use of hot-dip galvanizing for atmospheric corrosion protection of steel components is a prescribed method in the relevant standards for power transmission and transformation engineering design, and the design life is 30 to 50 years. Operation experience shows that the corrosion resistance life of hot-dip galvanizing is closely related to environmental characteristics. In general areas, the initial effective life is generally 15 to 30 years, and in heavy corrosion environments such as coastal areas and heavy industrial pollution areas, it is about 5 to 7 years. Relying on hot-dip galvanizing itself cannot meet the design life requirements in both environments.

[0004] Dacromet technology is a coating anti-corrosion technology applied to metal surfaces. Compared with traditional galvanizing technology, Dacromet coating has the advantages of high corrosion resistance, no hydrogen embrittlement, and heat resistance. Dacromet coating solution mainly includes zinc-aluminum powder, chromate, dispersant and other additives. However, chromate not only has a strong carcinogenic effect on the human body, but also has great harm to the ecological environment. With the enhancement of global environmental awareness, the chromate passivation film-forming method is abandoned, and the chromate-free Dacromet technology that uses chromate-free passivating agents, organic polymers and other chromium-free film-forming substances to replace chromate has received widespread attention from domestic and foreign researchers. At present, chromium-free Dacromet coatings mainly use silane or other organic matter as binders, and molybdate, phosphomolybdate, tungstate, etc. as passivators as substitutes for hexavalent chromium in Dacromet coatings, but their corrosion resistance needs to be improved compared with Dacromet coatings. Therefore, it is still urgent to develop a chromium-free Dacromet coating with high corrosion resistance. Summary of the invention

[0005] The embodiments of the present invention provide a chromium-free Dacromet coating, a coating preparation method and application thereof to solve the above-mentioned technical problems in the prior art.

[0006] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.

[0007] According to a first aspect of an embodiment of the present invention, a chromium-free Dacromet coating is provided.

[0008] In one embodiment, the chromium-free Dacromet coating comprises the following raw materials in parts by weight:

[0009] 17-50 parts of silane hydrolyzate containing photocatalyst, 27-56 parts of metal slurry, 0.6-1 parts of thickener, 0.6-1.2 parts of defoamer

[0010] In one embodiment, the silane hydrolyzate containing the photocatalyst comprises the following raw materials in parts by weight:

[0011] Carbon nitride C3N4 0.5-2 parts, corrosion inhibitor 0.2-1.2 parts, silane binder 4-10 parts, alcohol 6-15 parts, deionized water 5-20 parts, film-forming aid 0.2-1.5 parts.

[0012] In one embodiment, the metal slurry includes the following raw materials in parts by weight:

[0013] 14-30 parts of flaky zinc-aluminum alloy powder, 8-15 parts of protective agent, 4-10 parts of silane binder, and 0.1-1 part of wetting and dispersing agent.

[0014] In one embodiment, the corrosion inhibitor includes sodium phosphomolybdate, sodium molybdate or sodium silicate.

[0015] In one embodiment, the silane adhesive includes: AC-66 silane adhesive or AC-66E silane adhesive.

[0016] In one embodiment, the alcohol includes methanol or ethanol.

[0017] In one embodiment, the film-forming aid includes: OE-300 film-forming aid.

[0018] In one embodiment, the protective agent includes: polyethylene glycol-400 or ethylene glycol.

[0019] In one embodiment, the wetting and dispersing agent includes: VXW-6208 wetting and dispersing agent or Tween-20 wetting and dispersing agent.

[0020] In one embodiment, the particle size of the flaky zinc-aluminum alloy powder is 9-15 μm; the mass ratio of aluminum powder to zinc powder in the flaky zinc-aluminum alloy powder is 1:10-1:4.

[0021] In one embodiment, the thickener includes: hydroxyethyl cellulose or fumed silica.

[0022] In one embodiment, the defoamer includes: DC65 defoamer, BYK-092 defoamer or BYK-1781 defoamer.

[0023] According to a second aspect of an embodiment of the present invention, a method for preparing a chromium-free Dacromet coating is provided, and a coating is prepared using the chromium-free Dacromet coating.

[0024] In one embodiment, the method for preparing the chromium-free Dacromet coating comprises the following steps:

[0025] Preparing a silane hydrolyzate containing a photocatalyst and a metal slurry; and mixing and stirring the silane hydrolyzate containing the photocatalyst and the metal slurry to obtain a mixed slurry;

[0026] Adding a defoamer and a thickener to the mixed slurry and stirring, and performing ultrasonic dispersion (ultrasonic dispersion time is 3-10 minutes) and magnetic stirring treatment (magnetic stirring time is 3-6 hours) to obtain a chromium-free Dacromet coating with a photocatalytic function;

[0027] The obtained chromium-free Dacromet coating with photocatalytic function is sprayed on the pretreated coating carrier (Q235 carbon steel plate) by using a spray gun; and the sprayed coating carrier is subjected to multiple heating and heat preservation curing treatments (the multiple heating and heat preservation curing treatments are placed in a box furnace and kept at 70-85° C. for 20-30 minutes, and then programmed to heat to 260-300° C. and kept for 20-30 minutes), and the chromium-free Dacromet coating with photocatalytic function is obtained after natural cooling;

[0028] The pretreatment of the coating carrier is to roughen the surface of the Q235 carbon steel plate with sandpaper, clean the surface oil with anhydrous ethanol, and dry it for use. The thickness of the prepared chromium-free Dacromet coating with photocatalytic function is 12-20 μm.

[0029] In one embodiment, a method for preparing a silane hydrolyzate containing a photocatalyst comprises:

[0030] Put the carbon nitride C3N4 solid powder in a beaker, and add deionized water to perform ultrasonic dispersion treatment (ultrasonic dispersion treatment time is 30-60min) to obtain a carbon nitride C3N4 dispersion liquid;

[0031] Put the corrosion inhibitor in a beaker, stir and dissolve it with deionized water, then add alcohol and stir evenly to obtain a well-mixed alcohol-water solution;

[0032] A silane binder and a film-forming aid are added to an alcohol aqueous solution, the mixture is dispersed by stirring, and the obtained carbon nitride C3N4 dispersion is added thereto for magnetic stirring hydrolysis (hydrolysis time is 30-60 min) to obtain a silane hydrolyzate containing a photocatalyst.

[0033] In one embodiment, the preparation method of solid carbon nitride C3N4 comprises:

[0034] Obtain the raw material melamine (1.5 g), and evenly disperse the melamine in a porcelain boat, place the porcelain boat in a muffle furnace, and perform multiple heating and heat preservation treatments (set the heating program to 5°C / min to 500°C, keep it at 500°C for 1 hour, and then heat it to 550°C and keep it for 1 hour). After multiple heating and heat preservation treatments, naturally cool to room temperature to obtain a light yellow solid, which is solid carbon nitride C3N4.

[0035] In one embodiment, the method for preparing the metal slurry comprises:

[0036] The silane binder, protective agent and wetting dispersant are mixed evenly, and the flaky zinc-aluminum alloy powder is added and stirred evenly by magnetic force to obtain a metal powder slurry.

[0037] According to the third aspect of an embodiment of the present invention, an application of a chrome-free Dacromet coating is provided, and the above-mentioned chrome-free Dacromet coating or the chrome-free Dacromet coating prepared by the above-mentioned chrome-free Dacromet coating preparation method is applied to overhead transmission line connecting fittings.

[0038] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:

[0039] The present invention prepares the chrome-free Dacromet coating by utilizing silane hydrolyzate containing photocatalyst, metal slurry, thickener and defoamer, so that the prepared chrome-free Dacromet coating has photocatalytic effect, the photocatalyst generates photogenerated electron-hole pairs (i.e., photogenerated carriers) under sunlight irradiation, and the photogenerated carriers migrate through the interior of the material to reach the surface of the material, so that an electron-rich area is formed on the metal surface to avoid electron-loss corrosion of the metal, and at the same time, the coating surface can participate in the redox reaction of water, thereby achieving the photolysis target of water molecules, thereby inhibiting the corrosion of the steel substrate and improving the corrosion resistance.

[0040] In addition, the present invention uses carbon nitride as a photocatalyst and flaky zinc-aluminum alloy powder as a metal slurry raw material, so that carbon nitride can be used as a zinc-aluminum alloy powder filler carrier. By stacking flaky fillers, a denser coating parallel to the surface of the steel substrate can be formed, which increases the erosion process of the corrosive medium in the coating and improves the shielding ability of the coating.

[0041] In addition, due to its fine grains and low degree of component segregation, the flaky zinc-aluminum alloy powder avoids the problem of stratification of the coating due to uneven mixing of zinc powder and aluminum powder due to large differences in specific gravity, thereby improving the uniformity of the coating.

[0042] At the same time, the present invention uses a spray gun to spray the chromium-free Dacromet coating with photocatalytic function on the surface of the overhead power transmission line connecting hardware, the coating thickness is easy to control, the operation is simple, and it is easy to mass produce.

[0043] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0045] Figure 1 This is a SEM image of the coating prepared in Example 1;

[0046] Figure 2 This is the SEM image of the coating prepared in Comparative Example 1;

[0047] Figure 3 The results of the coating prepared in Example 1 after 1000 hours of neutral salt spray resistance;

[0048] Figure 4 The results of the coating prepared in Comparative Example 2 after 520 hours of neutral salt spray resistance;

[0049] Figure 5 The electrochemical polarization curves of the coatings prepared in Examples 1-5 and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION

[0050] The following description and accompanying drawings fully illustrate the specific embodiments of this article so that those skilled in the art can practice them. Parts and features of some embodiments may be included in or replace parts and features of other embodiments. The scope of the embodiments of this article includes the entire scope of the claims, as well as all available equivalents of the claims. Herein, the terms "first", "second", etc. are only used to distinguish one element from another, without requiring or implying any actual relationship or order between these elements. In fact, the first element can also be called the second element, and vice versa. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the structure, device or equipment including a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also include elements inherent to such structure, device or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the structure, device or equipment including the elements. Each embodiment is described in a progressive manner herein, and each embodiment focuses on the differences from other embodiments, and the same and similar parts between the embodiments can be referred to each other.

[0051] As used herein, the term "plurality" means two or more than two, unless otherwise specified.

[0052] In this document, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B means: A or B.

[0053] In this article, the term "and / or" is a description of the association relationship between objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or, A and B.

[0054] It should be understood that, although the various steps in the flow chart are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear description in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a portion of the steps in the figure may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these sub-steps or stages is not necessarily to be carried out in sequence, but can be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.

[0055] In the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0056] Example 1

[0057] Component A: carbon nitride C3N4 0.5g, sodium phosphomolybdate 0.2g, AC-66 silane binder 4.8g, methanol 6g, deionized water 5g, OE-300 film-forming aid 0.2g;

[0058] Component B: 14 g of flaky zinc-aluminum alloy powder (the mass ratio of aluminum powder to zinc powder is 1:5, and the particle size is 15 μm), 8 g of polyethylene glycol-400, 4.8 g of AC-66 silane binder, and 0.1 g of VXW-6208 wetting and dispersing agent.

[0059] Component C: 0.6g of fumed silica and 0.6g of DC65 defoamer.

[0060] The preparation method is as follows:

[0061] (1) Preparation of carbon nitride C3N4: Weigh 1.5 g of melamine and evenly disperse it in a porcelain boat. Place the porcelain boat in a muffle furnace and set the temperature program to rise to 500°C at 5°C / min. Keep the temperature at 500°C for 1 h, then heat the temperature to 550°C and keep the temperature for 1 h. After cooling naturally to room temperature, a light yellow solid is obtained, which is carbon nitride C3N4.

[0062] (2) Place carbon nitride C3N4 solid powder in a beaker, add appropriate amount of deionized water and sonicate for 30 minutes to obtain carbon nitride C3N4 dispersion;

[0063] (3) Weighing sodium phosphomolybdate in a beaker, stirring and dissolving it with deionized water, adding methanol and stirring evenly, adding AC-66 silane binder and OE-300 film-forming aid to the uniformly mixed alcohol-water solution and stirring and dispersing them, then adding the prepared carbon nitride C3N4 dispersion liquid to the mixed solution, and hydrolyzing it under magnetic stirring for 30 minutes to obtain component A silane hydrolyzate;

[0064] (4) mixing AC-66 silane binder, polyethylene glycol-400, and VXW-6208 wetting and dispersing agent uniformly, adding flaky zinc-aluminum alloy powder, and stirring uniformly with a magnetic force to obtain a metal powder slurry of component B;

[0065] (5) Mixing components A and B and stirring them evenly, then adding DC65 defoamer and fumed silica, stirring, ultrasonically dispersing for 3 minutes, and then magnetically stirring for 3 hours to obtain a chromium-free Dacromet coating with photocatalytic function;

[0066] (6) The surface of the Q235 carbon steel plate was roughened with sandpaper, the surface oil was cleaned with anhydrous ethanol, and it was dried for later use;

[0067] (7) taking a certain amount of chromium-free Dacromet coating with photocatalytic function and placing it in a gravity-type pneumatic spray gun, spraying it on the surface of the treated carbon steel plate, and controlling the coating thickness by controlling the coating spraying amount;

[0068] (8) The carbon steel plate sprayed with the coating was placed in a box furnace and kept at 70°C for 20 minutes, then the temperature was raised to 260°C and kept at this temperature for 20 minutes. After natural cooling, a chromium-free Dacromet coating with photocatalytic function was obtained.

[0069] In this embodiment, the thickness of the chromium-free Dacromet coating with photocatalytic function is about 12 μm.

[0070] Example 2

[0071] Component A: carbon nitride C3N4 0.5g, sodium phosphomolybdate 0.4g, AC-66 silane binder 5.6g, methanol 8g, deionized water 8g, OE-300 film-forming aid 0.4g;

[0072] Component B: 18g flaky zinc-aluminum alloy powder, 10g polyethylene glycol-400, 5.6g AC-66 silane binder, and 0.2g VXW-6208 wetting and dispersing agent.

[0073] Component C: 0.8g of fumed silica and 0.8g of DC65 defoamer.

[0074] The preparation method is as follows:

[0075] (1) Preparation of carbon nitride C3N4: Weigh 1.5 g of melamine and evenly disperse it in a porcelain boat. Place the porcelain boat in a muffle furnace and set the temperature program to rise to 500°C at 5°C / min. Keep the temperature at 500°C for 1 h, then heat the temperature to 550°C and keep the temperature for 1 h. After cooling naturally to room temperature, a light yellow solid is obtained, which is carbon nitride C3N4.

[0076] (2) Place carbon nitride C3N4 solid powder in a beaker, add appropriate amount of deionized water and sonicate for 30 minutes to obtain carbon nitride C3N4 dispersion;

[0077] (3) weighing sodium phosphomolybdate in a beaker, stirring and dissolving it with deionized water, adding methanol and stirring evenly, adding AC-66 silane binder and OE-300 film-forming aid to the uniformly mixed alcohol-water solution and stirring and dispersing them, then adding the prepared carbon nitride C3N4 dispersion to the mixed solution, and hydrolyzing it under magnetic stirring for 40 minutes to obtain component A silane hydrolyzate;

[0078] (4) mixing AC-66 silane binder, polyethylene glycol-400, and VXW-6208 wetting and dispersing agent uniformly, adding flaky zinc-aluminum alloy powder, and stirring uniformly with a magnetic force to obtain a metal powder slurry of component B;

[0079] (5) Mixing components A and B and stirring them evenly, then adding DC65 defoamer and fumed silica, stirring, ultrasonically dispersing for 5 minutes, and then magnetically stirring for 4 hours to obtain a chromium-free Dacromet coating with photocatalytic function;

[0080] (6) The surface of the Q235 carbon steel plate was roughened with sandpaper, the surface oil was cleaned with anhydrous ethanol, and it was dried for later use;

[0081] (7) taking a certain amount of chromium-free Dacromet coating with photocatalytic function and placing it in a gravity-type pneumatic spray gun, spraying it on the surface of the treated carbon steel plate, and controlling the coating thickness by controlling the amount of coating sprayed;

[0082] (8) The carbon steel plate sprayed with the coating was placed in a box furnace and kept at 75°C for 20 minutes, then the temperature was raised to 270°C and kept at this temperature for 20 minutes. After natural cooling, a chromium-free Dacromet coating with photocatalytic function was obtained.

[0083] In this embodiment, the thickness of the chromium-free Dacromet coating with photocatalytic function is about 14 μm.

[0084] Example 3

[0085] Component A: 1g carbon nitride C3N4, 0.6g sodium silicate, 7.2g AC-66 silane binder, 10g methanol, 10g deionized water, 0.8g OE-300 film-forming aid;

[0086] Component B: 20g flaky zinc-aluminum alloy powder, 12g polyethylene glycol-400, 7.2g AC-66 silane binder, and 0.3g VXW-6208 wetting and dispersing agent.

[0087] Component C: 1.0g meteorological silica, 1.0g DC65 defoamer.

[0088] The preparation method is as follows:

[0089] (1) Preparation of carbon nitride C3N4: Weigh 1.5 g of melamine and evenly disperse it in a porcelain boat. Place the porcelain boat in a muffle furnace and set the temperature program to rise to 500°C at 5°C / min. Keep the temperature at 500°C for 1 h, then heat the temperature to 550°C and keep the temperature for 1 h. After cooling naturally to room temperature, a light yellow solid is obtained, which is carbon nitride C3N4.

[0090] (2) Place carbon nitride C3N4 solid powder in a beaker, add appropriate amount of deionized water and sonicate for 40 minutes to obtain carbon nitride C3N4 dispersion;

[0091] (3) Weigh sodium silicate in a beaker, stir and dissolve it with deionized water, add methanol and stir evenly, stir and disperse carbon nitride C3N4 in the uniformly mixed alcohol-water solution, then add the prepared carbon nitride C3N4 dispersion to the mixed solution, and hydrolyze it for 30 minutes under magnetic stirring to obtain component A silane hydrolyzate;

[0092] (4) mixing AC-66 silane binder, polyethylene glycol-400, and VXW-6208 wetting and dispersing agent uniformly, adding flaky zinc-aluminum alloy powder, and stirring uniformly with a magnetic force to obtain a metal powder slurry of component B;

[0093] (5) Mixing components A and B, stirring evenly, then adding DC65 defoamer and fumed silica, stirring, ultrasonically dispersing for 7 minutes, and then magnetically stirring for 5 hours to obtain a chromium-free Dacromet coating with photocatalytic function;

[0094] (6) The surface of the Q235 carbon steel plate was roughened with sandpaper, the surface oil was cleaned with anhydrous ethanol, and it was dried for later use;

[0095] (7) taking a certain amount of chromium-free Dacromet coating with photocatalytic function and placing it in a gravity-type pneumatic spray gun, spraying it on the surface of the treated carbon steel plate, and controlling the coating thickness by controlling the coating spraying amount;

[0096] (8) The carbon steel plate sprayed with the coating was placed in a box furnace and kept at 80°C for 30 minutes, then the temperature was raised to 280°C and kept at this temperature for 30 minutes. After natural cooling, a chromium-free Dacromet coating with photocatalytic function was obtained.

[0097] In this embodiment, the thickness of the chromium-free Dacromet coating with photocatalytic function is about 15 μm.

[0098] Example 4

[0099] Component A: 1.5g carbon nitride C3N4, 0.8g sodium molybdate, 8.8g AC-66E silane binder, 12g ethanol, 15g deionized water, 1.2g OE-300 film-forming aid;

[0100] Component B: 25g flaky zinc-aluminum alloy powder, 14g ethylene glycol, 8.8g AC-66E silane binder, and 0.6g Tween-20 wetting and dispersing agent.

[0101] Component C: 1g of meteorological silica, 1.2g of DC65 defoamer.

[0102] The preparation method is as follows:

[0103] (1) Preparation of carbon nitride C3N4: Weigh 1.5 g of melamine and evenly disperse it in a porcelain boat. Place the porcelain boat in a muffle furnace and set the temperature program to rise to 500°C at 5°C / min. Keep the temperature at 500°C for 1 h, then heat the temperature to 550°C and keep the temperature for 1 h. After cooling naturally to room temperature, a light yellow solid is obtained, which is carbon nitride C3N4.

[0104] (2) Place carbon nitride C3N4 solid powder in a beaker, add appropriate amount of deionized water and sonicate for 50 minutes to obtain carbon nitride C3N4 dispersion;

[0105] (3) Weighing sodium phosphomolybdate in a beaker, stirring and dissolving it with deionized water, adding ethanol and stirring evenly, adding AC-66E silane binder and OE-300 film-forming aid to the mixed alcohol-water solution and stirring and dispersing them, then adding the prepared carbon nitride C3N4 dispersion to the mixed solution, and hydrolyzing it under magnetic stirring for 30 minutes to obtain component A silane hydrolyzate;

[0106] (4) Mixing AC-66E silane binder, ethylene glycol, and Tween-20 wetting and dispersing agent uniformly, adding flaky zinc-aluminum alloy powder, and stirring uniformly with a magnetic stirrer to obtain a metal powder slurry of component B;

[0107] (5) Mixing components A and B and stirring them evenly, then adding DC65 defoamer and fumed silica, stirring, ultrasonically dispersing for 9 minutes, and then magnetically stirring for 6 hours to obtain a chromium-free Dacromet coating with photocatalytic function;

[0108] (6) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;

[0109] (7) taking a certain amount of chromium-free Dacromet coating with photocatalytic function and placing it in a gravity-type pneumatic spray gun, spraying it on the surface of the treated carbon steel plate, and controlling the coating thickness by controlling the amount of coating sprayed;

[0110] (8) The carbon steel plate sprayed with the coating was placed in a box furnace and kept at 85°C for 20 minutes, then the temperature was raised to 290°C and kept at this temperature for 20 minutes. After natural cooling, a chromium-free Dacromet coating with photocatalytic function was obtained.

[0111] In this embodiment, the thickness of the chromium-free Dacromet coating with photocatalytic function is about 14 μm.

[0112] Example 5

[0113] Component A: 2g carbon nitride C3N4, 1.2g sodium phosphomolybdate, 10g AC-66E silane binder, 15g ethanol, 20g deionized water, 1.5 parts OE-300 film-forming aid;

[0114] Component B: 30g flaky zinc-aluminum alloy powder, 15g ethylene glycol, 10g AC-66E silane binder, and 1g Tween-20 wetting and dispersing agent.

[0115] Component C: 0.6 g hydroxyethyl cellulose, 0.6 g BYK-092 defoamer.

[0116] The preparation method is as follows:

[0117] (1) Preparation of carbon nitride C3N4: Weigh 1.5 g of melamine and evenly disperse it in a porcelain boat. Place the porcelain boat in a muffle furnace and set the temperature program to rise to 500°C at 5°C / min. Keep the temperature at 500°C for 1 h, then heat the temperature to 550°C and keep the temperature for 1 h. After cooling naturally to room temperature, a light yellow solid is obtained, which is carbon nitride C3N4.

[0118] (2) Place carbon nitride C3N4 solid powder in a beaker, add appropriate amount of deionized water and sonicate for 60 minutes to obtain carbon nitride C3N4 dispersion;

[0119] (3) Weighing sodium phosphomolybdate in a beaker, stirring and dissolving it with deionized water, adding ethanol and stirring evenly, adding AC-66E silane binder and OE-300 film-forming aid to the mixed alcohol-water solution and stirring and dispersing them, then adding the prepared carbon nitride C3N4 dispersion to the mixed solution, and hydrolyzing it under magnetic stirring for 30 minutes to obtain component A silane hydrolyzate;

[0120] (4) Mixing AC-66E silane binder, ethylene glycol, and Tween-20 wetting and dispersing agent uniformly, adding flaky zinc-aluminum alloy powder, and stirring uniformly with a magnetic stirrer to obtain a metal powder slurry of component B;

[0121] (5) Components A and B were mixed and stirred evenly, and then BYK-092 defoamer and hydroxyethyl cellulose were added and stirred, ultrasonically dispersed for 10 minutes, and then magnetically stirred for 6 hours to obtain a chromium-free Dacromet coating with photocatalytic function;

[0122] (6) The surface of the Q235 carbon steel plate was roughened with sandpaper, and the surface oil was cleaned with anhydrous ethanol and dried for later use;

[0123] (7) taking a certain amount of chromium-free Dacromet coating with photocatalytic function and placing it in a gravity-type pneumatic spray gun, spraying it on the surface of the treated carbon steel plate, and controlling the coating thickness by controlling the amount of coating sprayed;

[0124] (8) The carbon steel plate sprayed with the coating was placed in a box furnace and kept at 85°C for 20 minutes, then the temperature was raised to 300°C and kept at this temperature for 20 minutes. After natural cooling, a chromium-free Dacromet coating with photocatalytic function was obtained.

[0125] In this embodiment, the thickness of the chromium-free Dacromet coating with photocatalytic function is about 15 μm.

[0126] Comparative Example 1

[0127] The difference from Example 1 is that the addition of carbon nitride C3N4 is omitted, and the other parameters and steps are the same as those of Example 1.

[0128] Comparative Example 2

[0129] The difference from Example 1 is that the flaky zinc-aluminum alloy powder is replaced by a mixture of flaky zinc powder and flaky aluminum powder (the mass ratio of flaky aluminum powder to flaky zinc powder is 1:5), and the other parameters and steps are the same as those in Example 1.

[0130] Comparative Example 3

[0131] The difference from Example 1 is that the addition of carbon nitride C3N4 is omitted, and the flaky zinc-aluminum alloy powder is replaced by a mixture of flaky zinc powder and flaky aluminum powder (the mass ratio of flaky aluminum powder to flaky zinc powder is 1:5). The other parameters and steps are the same as those in Example 1.

[0132] The coatings prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests. The coating thickness test was based on standard GB / T13452.2-2008 "Determination of paint film thickness of paints and varnishes"; the adhesion test was based on standard GB / T 9286-2021 "Scratch test for paints and varnishes"; the salt water resistance test was based on standard GB / T9274-1988 "Determination of resistance of paints and varnishes to liquid media"; the neutral salt spray resistance test was based on GB / T10125-2021 "Artificial atmosphere corrosion test salt spray test"; the corrosion potential test adopted a three-electrode electrochemical test system, the counter electrode was a 1cm×1cm platinum electrode, the reference electrode was a saturated calomel electrode, the working electrode was the prepared test piece coated with the anti-corrosion coating, the electrolyte was a 3.5wt% NaCl solution, and the PARSTAT2273 electrochemical workstation was used.

[0133] The test results of the coating properties prepared in Examples 1-5 of the present invention and Comparative Examples 1-3 are shown in the following table:

[0134]

[0135] The above performance results show that the coating prepared by spraying has uniform thickness, and the coating prepared by spraying has controllable and uniform thickness; the adhesion of Examples 1-5 and Comparative Example 1 is all level 1, and the adhesion on the substrate surface is strong, while the adhesion of the coating prepared by Comparative Examples 2-3 is level 2. It can be seen that the adhesion of the coating prepared by mixing flaky zinc powder and flaky aluminum powder is worse than that of the coating prepared by adding zinc-aluminum alloy powder. This is because the difference in specific gravity between zinc powder and aluminum powder is large, which makes the coating prone to stratification, poor coating uniformity, and uneven adhesion on the substrate surface, resulting in reduced adhesion performance of the coating; from the salt water resistance and neutral salt spray resistance, it can be seen that the corrosion resistance of the present invention is excellent and better than that of Comparative Examples 1-3, indicating that the addition of carbon nitride C3N4 and flaky zinc-aluminum alloy powder makes the coating more uniform and dense, and the corrosion resistance of the coating is improved; in addition, from the electrochemical test corrosion potential, it can also be seen that the corrosion resistance of the coating prepared by Examples 1-5 is better than that of Comparative Examples 1-3, and the optimal corrosion potential is -1.02V, with excellent corrosion resistance.

[0136] The present invention adds carbon nitride C3N4 to the chromium-free Dacromet coating. Carbon nitride C3N4 has high thermal stability and chemical stability, and a narrow band gap (>420nm), and is widely used in the field of photocatalysis, such as photolysis of water to produce hydrogen, degradation of organic pollutants, etc. Photocatalytic decomposition of water is a process of converting water into hydrogen and oxygen under the action of a catalyst. Carbon nitride C3N4 acts as a semiconductor photocatalyst. When absorbing incident photons from sunlight, the ground state electrons on the valence band are excited and transition to the conduction band, thereby converting into excited state electrons, and at the same time, forming photogenerated electron-hole pairs (i.e., photogenerated carriers) with the positively charged holes left on the valence band. The photogenerated carriers are transferred from the bulk phase to the surface phase through transmission, and are oxidized and reduced with the water on the surface of the carbon nitride C3N4, thereby preventing the corrosive medium water from entering the coating to corrode the steel substrate.

[0137] The present invention is not limited to the structures which have been described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A chromium-free Dacromet coating, characterized in that: The invention comprises the following raw materials in parts by weight: The invention comprises 17-50 parts of silane hydrolyzate containing photocatalyst, 27-56 parts of metal powder slurry, 0.6-1 parts of thickener and 0.6-1.2 parts of defoamer.

2. A chromium-free Dacromet coating according to claim 1, characterized in that: The silane hydrolyzate containing the photocatalyst comprises the following raw materials in parts by weight: Carbon nitride C3N4 0.5-2 parts, corrosion inhibitor 0.2-1.2 parts, silane binder 4-10 parts, alcohol 6-15 parts, deionized water 5-20 parts, film-forming aid 0.2-1.5 parts; Or, the metal slurry comprises the following raw materials in parts by weight: 14-30 parts of flaky zinc-aluminum alloy powder, 8-15 parts of protective agent, 4-10 parts of silane binder, and 0.1-1 part of wetting and dispersing agent.

3. A chromium-free Dacromet coating according to claim 2, characterized in that: The corrosion inhibitor includes sodium phosphomolybdate, sodium molybdate or sodium silicate.

4. A chromium-free Dacromet coating according to claim 2, characterized in that: The silane adhesive includes: AC-66 type silane adhesive or AC-66E type silane adhesive.

5. A chromium-free Dacromet coating according to claim 2, characterized in that: The alcohol includes methanol or ethanol.

6. A chromium-free Dacromet coating according to claim 2, characterized in that: The film-forming aid includes: OE-300 film-forming aid.

7. A chromium-free Dacromet coating according to claim 2, characterized in that: The protective agent includes: polyethylene glycol-400 or ethylene glycol.

8. A chromium-free Dacromet coating according to claim 2, characterized in that: The wetting and dispersing agent includes: VXW-6208 wetting and dispersing agent or Tween-20 wetting and dispersing agent.

9. A chromium-free Dacromet coating according to claim 2, characterized in that: The particle size of the flaky zinc-aluminum alloy powder is 9-15 μm; the mass ratio of aluminum powder to zinc powder in the flaky zinc-aluminum alloy powder is 1:10-1:

4.

10. The chromium-free Dacromet coating according to claim 1, characterized in that: The thickener includes: hydroxyethyl cellulose or fumed silica.

11. A chromium-free Dacromet coating according to claim 1, characterized in that: The defoamer includes: DC65 defoamer, BYK-092 defoamer or BYK-1781 defoamer.

12. A method for preparing a chromium-free Dacromet coating, characterized in that: The method of preparing a coating using the chromium-free Dacromet coating described in any of claims 1 to 11 comprises the following steps: Preparing a silane hydrolyzate containing a photocatalyst and a metal slurry; and mixing and stirring the silane hydrolyzate containing the photocatalyst and the metal slurry to obtain a mixed slurry; Adding a defoamer and a thickener into the mixed slurry and stirring, and performing ultrasonic dispersion and magnetic stirring treatment to obtain a chromium-free Dacromet coating with a photocatalytic function; The obtained chromium-free Dacromet coating with photocatalytic function is sprayed on the pretreated coating carrier by using a spray gun; and the sprayed coating carrier is subjected to multiple heating and heat preservation curing treatments, and the chromium-free Dacromet coating with photocatalytic function is obtained after natural cooling.

13. The method for preparing a chromium-free Dacromet coating according to claim 12, characterized in that: The preparation method of the silane hydrolyzate containing the photocatalyst comprises: Putting carbon nitride C3N4 solid powder in a beaker, and adding deionized water for ultrasonic dispersion treatment to obtain carbon nitride C3N4 dispersion; Put the corrosion inhibitor in a beaker, stir and dissolve it with deionized water, then add alcohol and stir evenly to obtain a well-mixed alcohol-water solution; A silane binder and a film-forming aid are added to an alcohol aqueous solution, the mixture is dispersed by stirring, and the obtained carbon nitride C3N4 dispersion is added thereto, and hydrolysis is performed by magnetic stirring to obtain a silane hydrolyzate containing a photocatalyst.

14. The method for preparing a chromium-free Dacromet coating according to claim 13, characterized in that: The preparation method of solid carbon nitride C3N4 comprises: The raw material melamine is obtained and evenly dispersed in a porcelain boat, and the porcelain boat is placed in a muffle furnace for multiple heating and heat preservation treatments. After multiple heating and heat preservation treatments, it is naturally cooled to room temperature to obtain a light yellow solid, which is solid carbon nitride C3N4.

15. The method for preparing a chromium-free Dacromet coating according to claim 12, characterized in that: The preparation method of the metal slurry comprises: The silane binder, protective agent and wetting dispersant are mixed evenly, and the flaky zinc-aluminum alloy powder is added and stirred evenly by magnetic force to obtain a metal powder slurry.

16. An application of a chromium-free Dacromet coating, characterized in that: The chrome-free Dacromet coating described in any one of claims 1 to 11 or the chrome-free Dacromet coating prepared by the chrome-free Dacromet coating preparation method described in any one of claims 12 to 15 is applied to overhead power transmission line connection fittings.